Effectiveness of Border Security Governance in Preventing Crimes in Nimule Border Post South Sudan - Yol, Marial Chanuong; Mwangi, Samson Wokabi; Mwaeke, Panuel (Advances in Social Sciences Research Journal, 2022)
This paper uses data collected for an MA Thesis on the effectiveness of Border Security Governance in Preventing Crimes in Nimule Border Post South Sudan. The study assessed the nature of existing border security models at Nimule Border Post –South Sudan; to assessed the influence of administrative structures on border security at Nimule Border Post –South Sudan, established the effect of resource allocation on the quality of border security at Nimule Border Post –South Sudan, and finally determined law enforcement officers perceptions on best practices for border security governance at Nimule Border Post –South Sudan. This study was guided by two theories; The Contingency Theory and The Governance Theory. The study use a Descriptive Research Survey Design to investigate the problem under the study. Questionnaires were used to collect data from 75 senior members of the police and 10 Key Informants. Key informants guide was used to collect qualitative data from the Key Informants. Data was analysed with the aid of Statistical Package for Social Sciences (SPSS) and the results presented using tables, bar graphs and pie charts. According to this study the existing border security model is only composed of the local police. This is inconsistent with the new international security model that require a coordinated multipronged approach by other public agencies. This explains the runaway insecurity prevalent in south Sudan and worse in areas around Nimule border itself. This administrative structure is organized in para- military style that limit and affect decision making of street officers at the Nimule border and characteristically discouraged free hand in operational contexts thus stifled security operations at the Nimule border. The study also established allocation of very scanty resources that did not support adoption of modern state of the arts border security technology at the Nimule border. According to this study law enforcement perceptions sought for the establishment of; joint border crossing points, international cooperation, border community policing programs, establishment of border communities in border security management and coordinated cross-border patrols and multiagency operations. As a policy matter, the government should bench mark with developed countries of best border security model which requires a coordinated multipronged approach by other public agencies and conform to it if she is to cut the problem of border insecurity to the nib. Further, decentralize and demilitarize the administrative structure which are a characteristic of hierarchical leadership structures and strict command and give officers on the street a free hand in decision making at the Nimule Border.